DIAGNOSIS OF CONGENITAL CMV IN CHILDREN IN THE FIRST YEAR OF LIFE - Daminov F. A.; Djabbarova N. R.; Negmatova Sh. M. (Web of Journals Publishing, 2025)
Unfortunately, many UTIs in the newborn period do not have a specific clinical picture and diagnosis of TORCH-infections only by clinical manifestations (without involving specific microbiological studies) leads to diagnostic errors in 90-95% of cases. The diagnosis of UTI is substantiated by the totality of: - anamnestic, - clinical - laboratory data [20,21,22,23].
Keywords: Newborns, high-risk groups, antenatal infections, PCR, IgG, IgM.